Ultraviolet / blue light enhanced rare earth nano composite material, preparation method and application in acrylate photopolymerization
By designing rare earth nanocomposites with luminescent layer, energy capture layer and pyridine-2-formic acid modification, the problem of poor photopolymerization reaction of existing rare earth nanocomposites in the ultraviolet/blue light area is solved, and efficient ultraviolet/blue light is achieved Improved effects of upconversion emission and photopolymerization.
Patent Information
- Application Number
- CN202510055354.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The poor photopolymerization effect of existing rare earth nanocomposites in the ultraviolet/blue light region limits their application in fields such as 3D printing.
By designing a rare earth nanocomposite material including a light emitting layer, a first energy capture layer and a second energy capture layer, and modifying pyridine-2-formic acid on its surface, the organic coordination molecular layer is to form an energy transfer channel to improve excitation light Energy capture capability.
Significantly improve the upconversion emission intensity of the UV/Blue Light region, improve the photopolymerization reaction effect, and can generate efficient upconversion emission within the UV/Blue Light spectrum range, meeting the demand for rapid polymer molding induced by UV/Blue Light .
Smart Images

Figure CN119463879A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing materials, and in particular to an ultraviolet / blue light enhanced rare earth nanocomposite material, a preparation method and application thereof in acrylate photopolymerization. Background Art
[0002] Lanthanide elements (Ln 3+ ) doped nanomaterials have the characteristics of narrow emission band, good chemical stability, long emission lifetime, low photobleaching, low toxicity and strong penetration ability. And Ln 3+ With rich energy levels, its absorption and emission energy spectra can cover from ultraviolet to near-infrared regions. Therefore, this type of material shows excellent application value in photocatalysis, optical storage, anti-counterfeiting and light-induced polymer polymerization reactions. Although lanthanide-doped nanomaterials have rich luminescence bands, it is still a major challenge to achieve efficient upconversion luminescence in the ultraviolet / blue light region. This challenge hinders their practical application in various fields. In recent years, core-shell structure engineering has been proven to be an effective material design method that can greatly improve the intensity of luminescence from ultraviolet to near-infrared, especially in the deep ultraviolet / blue light region, thereby expanding the application range of rare earth nanomaterials.
[0003] Photopolymerization processes are widely used in various fields of science, industry and technology, including direct laser writing, three-dimensional micromachining, holography, microelectronics and optoelectronics, optical component formation, data recording and storage, etc. Generally, this means converting a liquid mixture of photopolymerizable monomers or oligomers and photoinitiators (called photocurable compositions or PCCs) into solid materials under light irradiation. Light-based triggering is the key advantage of this technology, which allows high spatial and temporal resolution to be achieved in a non-contact manner. Single-photon polymerization is usually activated by ultraviolet or blue light irradiation, but lacks the repeated steps of adding subsequent polymer layers and is therefore mainly suitable for the fabrication of two-dimensional structures. This limitation is attributed to temporal and spatial constraints. First, the high light absorption rate of the photoinitiator leads to the formation of stable free radicals and the immediate triggering of the polymerization process. In addition, existing rare earth nanocomposites have only single-phase energy transfer channels, and the penetration depth of ultraviolet and visible light is limited by exponential light attenuation, which is limited to shallow layers, making the photopolymerization reaction poor, and linear light absorption limits the direct generation of 3D bulk structures with uniform density. Summary of the invention
[0004] The invention provides an ultraviolet / blue light enhanced rare earth nanocomposite material, a preparation method and an application thereof, so as to solve the technical problem that the existing rare earth nanocomposite material has a poor photopolymerization reaction effect.
[0005] According to a first aspect of the present invention, there is provided an ultraviolet / blue light enhanced rare earth nanocomposite material, the rare earth nanocomposite material comprising a rare earth nanomaterial and an organic coordination molecule layer disposed on the surface of the rare earth nanomaterial; the rare earth nanomaterial comprising a light-emitting layer and a first energy capture layer disposed outside the light-emitting layer, an energy transfer channel being formed between the first energy capture layer and the light-emitting layer; The main component of the organic coordination molecule layer is pyridine-2-carboxylic acid; The light-emitting layer contains Yb 3+ 、Tm 3+ Materials containing Yb 3+ , Gd 3+ 、Tm 3+ Materials containing Yb 3+ , Er 3+ Materials containing Gd 3+ 、Tm 3+ 、Ce 3+ At least one of the materials; The first energy capture layer contains Yb 3+ Materials containing Nd 3+ Materials containing Er 3+ Materials containing Yb 3+ 、Nd 3+ at least one of the materials.
[0006] Furthermore, the rare earth nanomaterial further comprises a second energy capture layer disposed inside the light-emitting layer, and an energy transfer channel is formed between the second energy capture layer and the light-emitting layer; The second energy capture layer contains Yb 3+ Materials containing Nd 3+ Materials containing Er 3+ Materials containing Yb 3+ 、Nd 3+ at least one of the materials.
[0007] Further, the thickness of the second energy capture layer is 5-40 nm; The thickness of the light-emitting layer is 2-10 nm; The thickness of the first energy capture layer is 2-10 nm.
[0008] Furthermore, the matrix material of the second energy capture layer, the light-emitting layer and the first energy capture layer is ALnF4 or AF2, wherein A is Li, Na, K or Ca; and Ln is La, Lu, Yb, Gd or Y.
[0009] Furthermore, the Yb in the second energy capture layer 3+ The molar fraction of ions is 90%~100%, or Nd3+ The molar fraction of ions is 50%~100%, or Er 3+ The molar fraction of ions is 90%~100%.
[0010] The Yb 3+ The molar fraction of ions is 30%~70%, and / or Tm 3+ The molar fraction of ions is 0.2%~1.5%, and / or Er 3+ The molar fraction of ions is 0.2%~3%, and / or Gd 3+ The molar fraction of Ce ions is 40%~60%, or 3+ The molar fraction of ions is 0.2%~5%.
[0011] The first energy capture layer contains Yb 3+ The molar fraction of ions is 5%~20%, and / or Nd 3+ The molar fraction of ions is 1%~20%, or Er 3+ The molar fraction of ions is 1%~25%.
[0012] According to the second aspect of the present invention, there is also provided a use of the ultraviolet / blue light enhanced rare earth nanocomposite material in acrylate photopolymerization.
[0013] Furthermore, the rare earth nanocomposite material is used to prepare 3D printing materials.
[0014] Furthermore, preparing the 3D printing material comprises the following steps: The rare earth nanocomposite material is mixed with a photocurable composition to form a liquid prepolymer; the prepolymer is the 3D printing material.
[0015] According to a third aspect of the present invention, there is also provided a method for preparing an ultraviolet / blue light enhanced rare earth nanocomposite material, comprising the following steps: S1: Preparation of rare earth nanomaterials; S2: removing the ligands on the surface of the rare earth nanomaterial to obtain a ligand-free rare earth nanomaterial, adding a pyridine-2-carboxylic acid solution to the solution of the ligand-free rare earth nanomaterial, and subjecting the solution to centrifugal treatment to obtain a rare earth nanocomposite material.
[0016] Furthermore, the preparation of the rare earth nanomaterial comprises the following steps: S1.1: dissolving rare earth salt A in a solvent to obtain a precursor A; reacting the precursor A under the conditions of a sodium source and a fluorine source to obtain a second energy capture layer; S1.2: dissolving a rare earth salt B in a solvent to obtain a precursor B; mixing the second energy capture layer with the precursor B, and encapsulating the second energy capture layer in the presence of a sodium source and a fluorine source to obtain a core-shell structured nanocrystal comprising the second energy capture layer and the light-emitting layer; S1.3: Dissolve the rare earth salt C in a solvent to obtain a precursor C; mix the core-shell structured nanocrystals with the precursor C, and wrap the core-shell structured nanocrystals in the presence of a sodium source and a fluorine source to obtain a rare earth nanomaterial with a core-shell-shell structure having, from the inside to the outside, a second energy capture layer, a light-emitting layer, and a first energy capture layer.
[0017] The present invention has the following beneficial effects: The rare earth nanocomposite material of the present invention comprises a rare earth nanomaterial and an organic coordination molecule layer arranged on the surface of the rare earth nanomaterial, wherein the luminescent layer in the rare earth nanoparticle is used for capturing energy and emitting light, and the first energy capturing layer is used for additionally obtaining excitation energy and transmitting it to the luminescent layer to form an energy transfer channel, thereby improving the excitation light energy capturing capability, reducing the loss of excitation energy on the surface, improving the luminescence intensity, promoting photopolymerization reaction, and achieving the purpose of improving the photopolymerization reaction effect; the pyridine-2-carboxylic acid molecule of the organic coordination molecule layer is a rigid structure, which can inhibit the interaction between rare earth ions on the surface of the rare earth nanomaterial and solvent molecules, and inhibit the quenching caused by surface defects or vacancies, greatly reducing multi-phonon non-radiative transitions, and in addition, the N, O-hybridized coordination sites in the molecules form coordination bonds with the rare earth ions on the surface of the rare earth nanomaterial, so that the energy gap between the orbits of the occupied electrons and the empty orbits of the rare earth ions on the surface of the rare earth nanomaterial is equivalent to the energy gap of the rare earth ions inside the rare earth nanomaterial, which can promote the energy transfer from the outside to the inside, and further improve the luminescence efficiency.
[0018] The rare earth nanocomposite material of the present invention can generate efficient up-conversion emission in the ultraviolet / blue light spectrum range under the excitation of near-infrared light such as ~740 nm, ~793 nm, ~808 nm, ~980 nm or ~1532 nm, greatly improving the ultraviolet / blue light up-conversion luminescence intensity, thereby enhancing the photopolymerization reaction effect to meet the demand for rapid prototyping of high molecular polymers induced by ultraviolet / blue light.
[0019] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention will be further described in detail below. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1This is a transmission electron microscope photo of NaYbF4@NaGdF4:Yb, Tm@NaLuF4:Yb nanoparticles in Example 1 of the present invention; Figure 2 This is a high-angle annular dark field (HAADF) scanning transmission electron microscope (STEM) image of the NaYbF4@NaGdF4:Yb, Tm@NaLuF4:Yb nanomaterial in Example 1 of the present invention; Figure 3 The luminescence spectrum of the multiphase energy capture rare earth nanomaterial of Example 1 of the present invention; Figure 4 This is a comparative spectrum of the luminescence intensity of the rare earth nanomaterial in Example 1 of the present invention and the nanomaterial modified with pyridine-2-carboxylic acid in Example 2; Figure 5 Schematic diagram of energy transfer in nanomaterials with unmodified and modified pyridine-2-carboxylic acid layers; Figure 6 This is the 3D printed shape finally obtained in Example 5 of the present invention. DETAILED DESCRIPTION
[0021] The embodiments of the present invention are described in detail below with reference to the accompanying drawings. However, the present invention can be implemented in many different ways as defined and covered below.
[0022] The embodiment of the first aspect of the present invention provides an ultraviolet / blue light enhanced rare earth nanocomposite material, the rare earth nanocomposite material comprising a rare earth nanomaterial and an organic coordination molecule layer disposed on the surface of the rare earth nanomaterial; the rare earth nanomaterial comprises a light-emitting layer and a first energy capture layer disposed outside the light-emitting layer, an energy transfer channel is formed between the first energy capture layer and the light-emitting layer; The main component of the organic coordination molecule layer is pyridine-2-carboxylic acid, and pyridine-2-carboxylic acid forms coordination bonds with the rare earth ions of the first energy capture layer to promote energy transfer.
[0023] The light-emitting layer contains Yb 3+ 、Tm 3+ Materials containing Yb 3+ , Gd 3+ 、Tm 3+ Materials containing Yb 3+ , Er 3+ Materials containing Gd 3+ 、Tm 3+ 、Ce 3+ At least one of the materials; The first energy capture layer contains Yb 3+ Materials containing Nd 3+ Materials containing Er 3+ Materials containing Yb 3+、Nd 3+ at least one of the materials.
[0024] The rare earth nanocomposite material of the present invention comprises a rare earth nanomaterial and an organic coordination molecule layer arranged on the surface of the rare earth nanomaterial, wherein the luminescent layer in the rare earth nanoparticle is used for capturing energy and emitting light, and the first energy capturing layer is used for additionally obtaining excitation energy and transferring it to the luminescent layer to form an energy transfer channel, thereby improving the excitation light energy capturing capability, reducing the excitation energy loss on the surface, increasing the luminescent intensity, promoting the photopolymerization reaction, and achieving the purpose of improving the photopolymerization reaction effect. The pyridine-2-carboxylic acid molecules in the organic coordination molecule layer are rigid structures, which can inhibit the interaction between the rare earth ions on the surface of the rare earth nanomaterial and the solvent molecules, and inhibit the quenching caused by surface defects or vacancies, greatly reducing multi-phonon non-radiative transitions. In addition, the N, O-hybrid coordination sites in the molecules form a five-membered chelate ring with the rare earth ions of the first energy capture layer on the surface of the rare earth nanomaterial, such as the Yb³⁺ ion. The hybrid orbits formed thereby increase the 4f energy level occupied by the surface rare earth ions and reduce their empty 4f energy level. Therefore, the energy gap between the orbits occupied by the electrons of the rare earth ions in the first energy capture layer and the empty orbits is equivalent to the energy gap of the rare earth ions in the light-emitting layer and the second energy capture layer inside the rare earth nanomaterial, which can promote energy transfer from the outside to the inside and further improve the luminescence efficiency.
[0025] In a preferred embodiment, the rare earth nanomaterial further includes a second energy capture layer disposed inside the luminescent layer, and an energy transfer channel is formed between the second energy capture layer and the luminescent layer. 3+ Materials containing Nd 3+ Materials containing Er 3+ Materials containing Yb 3+ 、Nd 3+ At least one of the materials. The rare earth nanomaterials include a second energy capture layer, a luminescent layer and a first energy capture layer from the inside to the outside, forming a rare earth nanomaterial with a core-shell-shell structure. Under the excitation of near-infrared light, the second energy capture layer and the first energy capture layer can absorb energy at the same time and transfer it to the middle luminescent layer to form a two-phase energy transfer channel, thereby achieving luminescence enhancement in the ultraviolet to visible light region of the rare earth nanocomposite material and further improving the photopolymerization reaction effect.
[0026] Preferably, the thickness of the second energy capture layer is 5-40 nm; the thickness of the light-emitting layer is 2-10 nm; and the thickness of the first energy capture layer is 2-10 nm.
[0027] The luminescent layer of the core-shell-shell rare earth nanoparticles is doped with a sensitizer and a luminescent center for capturing energy and emitting light. The second energy capture layer and the first energy capture layer are also doped with a certain concentration of sensitizer for additionally obtaining excitation energy. The second energy capture layer and the first energy capture layer transfer energy to the luminescent layer, thereby forming a two-phase energy transfer channel. The sensitizer includes Yb 3+ 、Nd 3+ , Er 3+ etc., while Yb 3+ 、Nd 3+ , Er 3+ It can also serve as a luminescence center. A luminescence center is an ion that can receive energy and convert the received energy into light, such as Yb 3+ 、Nd 3+ , Er 3+ The near infrared light is infrared light with a wavelength of 740 nm, 793 nm, 808 nm, 980 nm, 1532 nm, etc. The preferred grafting amount of the organic coordination molecule layer is 500 to 10,000 molecules on the surface of each core-shell-shell structure rare earth nanoparticle. The present invention utilizes the organic coordination molecule layer and the core-shell-shell structure rare earth nanoparticles to construct an efficient energy transfer channel, ultimately achieving the purpose of ultraviolet / blue light enhancement, thereby improving the photopolymerization reaction effect.
[0028] In an embodiment of the present invention, the matrix materials of the second energy capture layer, the light-emitting layer and the first energy capture layer are ALnF4 or AF2, wherein A is Li, Na, K or Ca; and Ln is La, Lu, Yb, Gd or Y. The matrix materials of the second energy capture layer, the light-emitting layer and the first energy capture layer are selected according to specific requirements and may be the same or different.
[0029] In an embodiment of the present invention, Yb 3+ The molar fraction of ions is 90%~100%, or Nd 3+ The molar fraction of ions is 50%~100%, or Er 3+ The molar fraction of ions is 90%~100%.
[0030] In the second energy capture layer, Yb 3+ 、Nd 3+ , Er 3+ The concentration needs to be higher. If the concentration is lower than the above range, the luminescence will be weaker. If the concentration is higher than the above range, cross relaxation will occur, resulting in weaker luminescence.
[0031] In an embodiment of the present invention, Yb 3+ The molar fraction of ions is 30%~70%, and / or Tm 3+The molar fraction of ions is 0.2%~1.5%, and / or Er 3+ The molar fraction of ions is 0.2%~3%, and / or Gd 3+ The molar fraction of Ce ions is 40%~60%, or 3+ The molar fraction of ions is 0.2%~5%.
[0032] In the light-emitting layer, the above Yb 3+ , Er 3+ 、Tm 3+ , Gd 3+ 、Ce 3+ The concentration is in the optimal range. If the concentration is lower than the above range, the luminescence is weaker. If the concentration is higher than the above range, cross relaxation will occur, resulting in weaker luminescence.
[0033] In an embodiment of the present invention, Yb in the first energy capture layer 3+ The molar fraction of ions is 5%~20%, and / or Nd 3+ The molar fraction of ions is 1%~20%, or Er 3+ The molar fraction of ions is 1%~25%.
[0034] In the first energy capture layer, the Yb 3+ 、Nd 3+ , Er 3+ The concentration is in the optimal range. If the concentration is lower than the above range, the luminescence is weaker. If the concentration is higher than the above range, cross relaxation will occur, resulting in weaker luminescence.
[0035] The embodiment of the second aspect of the present invention provides a method for preparing an ultraviolet / blue light enhanced rare earth nanocomposite material, comprising the following steps: S1: Preparation of rare earth nanomaterials; S1.1: dissolving rare earth salt A in a solvent to obtain a precursor A; reacting the precursor A under the conditions of a sodium source and a fluorine source to obtain a second energy capture layer, wherein the size of the second energy capture layer is 5-40 nm; S1.2: dissolving a rare earth salt in a solvent to obtain a precursor B; mixing the second energy capture layer with the precursor B, and in the presence of a sodium source and a fluorine source, performing a shell coating on the second energy capture layer to obtain a core-shell structured nanocrystal comprising a second energy capture layer and a light-emitting layer; the shell layer here is the light-emitting layer, and the thickness of the light-emitting layer is 2-10 nm; S1.3: dissolving rare earth salt C in a solvent to obtain precursor C; mixing core-shell structured nanocrystals with precursor C, and encapsulating the core-shell structured nanocrystals in the presence of a sodium source and a fluorine source to obtain a rare earth nanomaterial having a core-shell-shell structure, which has a second energy capture layer, a light-emitting layer, and a first energy capture layer from the inside to the outside; the outermost shell layer is the first energy capture layer, and the thickness of the first energy capture layer is 2-10 nm; S2: removing the ligands on the surface of the rare earth nanomaterial to obtain a ligand-free rare earth nanomaterial, adding a pyridine-2-carboxylic acid solution to the solution of the ligand-free rare earth nanomaterial, and subjecting the solution to centrifugal treatment to obtain a rare earth nanocomposite material.
[0036] Preferably, the oleic acid-coated rare earth nanomaterial is dispersed in a hydrochloric acid solution and subjected to ultrasonic treatment for 5 minutes to remove surface ligands. Subsequently, the product is collected by centrifugation, washed with ethanol for multiple times, and finally redispersed in deionized water. A pyridine-2-carboxylic acid solution is added to the ligand-free nanoparticle solution. After the mixed solution is ultrasonically treated for 5 hours, the resulting clear solution is centrifuged to obtain a colloidal solid. The solid is washed with ethanol for several times and then redispersed in ethanol.
[0037] Specifically, the preparation method of the core-shell-shell structured rare earth nanoparticles is: a. Precursor preparation: Dissolve at least one rare earth salt selected from ytterbium salt (sensitizer), neodymium salt (sensitizer), gadolinium salt (luminescence center), thulium salt (luminescence center), yttrium salt (host material), and lutetium salt (host material) in a mixed solvent of oleic acid and octadecene at 140-170°C. o C for 0.5-3 h to obtain a precursor; The ytterbium salt is at least one of YbCl3, Yb(NO3)3, Yb(CH3CO2)3, Yb(TFA)3, and Yb(ACAC)3; The neodymium salt is at least one of NdCl3, Nd(NO3)3, Nd(CH3CO2)3, Nd(TFA)3, and Nd(ACAC)3; The gadolinium salt is at least one of GdCl3, Gd(NO3)3, Gd(CH3CO2)3, Gd(TFA)3, and Gd(ACAC)3; The thulium salt is at least one of TmCl3, Tm(NO3)3, Tm(CH3CO2)3, Tm(TFA)3, and Tm(ACAC)3; The yttrium salt is at least one of YCl3, Y(NO3)3, Y(CH3CO2)3, Y(TFA)3, and Y(ACAC)3; The lutetium salt is at least one of LuCl3, Lu(NO3)3, Lu(CH3CO2)3, Lu(TFA)3, and Lu(ACAC)3; b. Preparation of the second energy capture layer by high temperature decomposition: The precursor is heated at 220-330°C in the presence of a sodium source and a fluorine source. o C for 0.5-3 h to obtain the second energy capture layer; The sodium source is at least one of NaOH, NaF, and NaTFA; the fluorine source is at least one of NH4F, NaF, and trifluoroacetic acid rare earth complex; c. Preparation of rare earth luminescent multilayer core-shell structure materials: The material of the second energy capture layer is mixed with the precursor prepared in step a to obtain a reaction mixture, and the reaction mixture is reacted in the presence of a sodium source and a fluorine source to encapsulate the upconversion nanomaterial particles of the second energy capture layer to obtain core-shell structure nanocrystals. Step c is repeated to obtain a core-shell-shell structure, and then the reaction product oil-soluble heterogeneous rare earth nanocrystals are washed and dissolved in cyclohexane to obtain a rare earth nanomaterial solution.
[0038] According to an embodiment of the third aspect of the present invention, there is also provided a use of the ultraviolet / blue light enhanced rare earth nanocomposite material in acrylate photopolymerization.
[0039] Preferably, the rare earth nanocomposite material is photopolymerized in acrylate to prepare 3D printing material.
[0040] In an embodiment of the present invention, the method for preparing the 3D printed material comprises the following steps: (1) Synthetic 3D printing materials The rare earth nanocomposite material (UCNPs) is mixed with a photocurable composition, ultrasonically treated, and then the solvent is evaporated by vacuum drying to form a liquid prepolymer; the prepolymer is the 3D printing material.
[0041] Preferably, the photocurable composition comprises a photoinitiator Irgacure 369, oligocarbonate methacrylate (OCM-2) and polymethyl methacrylate (PMMA); (2) Preparation of 3D structural materials Near-infrared light can penetrate the 3D printing material, and the 3D printing material can initiate polymerization of acrylate under the excitation of the near-infrared laser and solidify to form a 3D structural material.
[0042] Under the excitation of a near-infrared semiconductor laser, a collimated laser beam is focused through an objective lens into a liquid prepolymer containing embedded UCNPs, allowing near-infrared light to radiate and penetrate the photocurable mixture to initiate polymerization of acrylates. After fabrication is completed, the sample is developed in 2-propanol to remove the unpolymerized photocurable composition (photoinitiator, oligocarbonate methacrylate, polymethyl methacrylate) to form a 3D structured material.
[0043] In an embodiment of the present invention, the excitation power wavelength of the near-infrared light in step (2) is ~740 nm, ~793 nm, ~808 nm, ~980 nm or ~1532 nm. The excitation wavelength selected as the excitation light source depends on the sensitizer. When Yb is selected as the sensitizer, a ~980 nm excitation light source is used; when Nd is selected as the sensitizer, a ~740 nm, ~793 nm, ~808 nm excitation light source is used; when Er is selected as the sensitizer, a ~808 nm or ~1532 nm excitation light source is used; the excitation power density is 10~30 Wcm -2 .
[0044] The following examples describe the present disclosure in more detail, and these examples are intended for illustrative purposes only.
[0045] Example 1
[0046] This embodiment provides a method for preparing a UV / blue light enhanced rare earth nanomaterial, wherein the rare earth nanoparticles with a core-shell-shell structure are NaYbF4@NaGdF4:Yb, Tm@NaLuF4:Yb, and the method comprises the following steps: Step A: Synthesis of NaYbF4 bare core First, 0.8 mmol of Yb(CH3CO2)3·xH2O aqueous solution, 10 mL of oleic acid and 10 mL of 1-octadecene liquid were added to a 50 mL three-necked flask, heated to 150 °C, and stirred for 60 min to generate a rare earth complex to obtain a precursor A solution; then, the temperature was lowered to room temperature, 6.4 mmol of sodium oleate solid powder was added to the precursor A solution, and the temperature was raised to 100 °C and stirred for 1 h under vacuum conditions; next, the mixed solution was filled with nitrogen and 3.2 mmol of NH3F solid powder was added, and the temperature was raised to 160 °C and reacted under nitrogen protection for 1.5 h; finally, the mixed solution was vacuumed for 10 min, and the temperature was raised to 320 °C under nitrogen protection for 30 min, then cooled to room temperature, washed with anhydrous ethanol and cyclohexane, and the obtained core nanoparticles were dispersed in 4 mL of cyclohexane to obtain core nanoparticles NaYbF with a diameter of 20 nm. 4; Step B: Synthesis of NaYbF4@NaGdF4:Yb,Tm core-shell nanoparticles The molar concentration ratio is Tm 3+ :Yb 3+ :Gd 3+ =1:55:45, take a total of 0.4 mmol of Tm(CH3CO2)3·xH2O, Yb(CH3CO2)3·xH2O, and Gd(CH3CO2)3·xH2O aqueous solution with a fixed ratio and add it to a 50 mL three-necked flask, add 5 mL of oleic acid and 5 mL of 1-octadecene liquid, heat to 150 °C, stir for 60 min, generate rare earth complexes, and obtain precursor B solution; when the temperature drops to 80 °C, add the core nanoparticle solution dispersed in 2 mL of cyclohexane obtained in step A to the precursor B solution, and stir for 30 min to remove cyclohexane in the system, when the temperature drops to 50 °C, quickly add 5 mL of methanol solution containing 1 mmol NaOH and 1.36 mmol NH4F, and stir for 30 min to obtain a mixed solution; then heat the mixed solution to 100 °C, evacuate for 5 min, and then fill with nitrogen for 1 min, and repeated three times. After removing methanol and oxygen from the reaction system, the temperature was raised to 300 °C and the reaction was carried out under the protection of nitrogen for 1.5 h. The obtained product was then cooled to room temperature and washed with anhydrous ethanol and cyclohexane to obtain NaYbF4@NaGdF4:49%Yb,1%Tm core-shell nanomaterials dispersed in 4 mL of cyclohexane with a diameter of about 30 nm. Step C: Synthesis of NaYbF4@NaGdF4:Yb,Tm@NaLuF4:Yb core-shell-shell nanoparticles The molar concentration ratio is Lu 3+ :Yb 3+=90:10, take 0.4 mmol of Lu(CH3CO2)3·xH2O and Yb(CH3CO2)3·xH2O aqueous solution with a fixed ratio and add it into a 50 mL three-necked flask, add 3 mL of oleic acid and 7 mL of 1-octadecene liquid, heat to 150 °C, stir for 30-60 min to generate rare earth complexes, and obtain precursor C solution. When the temperature drops to 80°C, the core-shell nanomaterial solution dispersed in 4 mL of cyclohexane obtained in step B is added to the precursor C solution, and stirred for 30 min to remove the cyclohexane in the system. When the temperature drops to 50°C, 5 mL of methanol solution containing 1 mmol NaOH and 1.36 mmol NH4F is quickly added and stirred for 30 min to obtain a mixed solution. The mixed solution is then heated to 100°C, vacuumed for 5 min, and then filled with nitrogen for 1 min, and repeated three times. After removing methanol and oxygen from the reaction system, the temperature is raised to 300°C, and the reaction is carried out under the protection of nitrogen for 1.5 h. The obtained product is then cooled to room temperature, washed with anhydrous ethanol and cyclohexane, and the obtained NaYbF4@NaGdF4:Yb, Tm@NaLuF4:Yb core-shell-shell upconversion nanoparticle luminescent material is dispersed in 4 mL of cyclohexane, and the material diameter is about 40 nm.
[0047] See also Figures 1 to 3 , Figure 1 The transmission electron microscope images of NaYbF4@NaGdF4:Yb,Tm@NaLuF4:Yb nanoparticles in Example 1 are shown in Figure a: NaYbF4 nanocore; Figure b: NaYbF4@NaGdF4:Yb,Tm core-shell structure; Figure c: NaYbF4@NaGdF4:Yb,Tm@NaLuF4:Yb core-shell-shell structure. The TEM images show that the synthesized nanomaterials have good morphology and uniform size, and the size of the material increases with the growth of the shell layer.
[0048] Figure 2 This is a high-angle annular dark field (HAADF) scanning transmission electron microscope (STEM) image of the NaYbF4@NaGdF4:Yb, Tm@NaLuF4:Yb nanomaterial in Example 1. The image shows that the synthesized nanomaterial has a single crystal structure.
[0049] Figure 3 This is the luminescence spectrum of the multiphase energy capture rare earth nanomaterial in Example 1. 253, 273, 176, 279, and 311 nm are for Gd 3+ The luminescence of 290, 345, 360, 450, 475, 511, and 650 nm are Tm 3+ The glow.
[0050] Example 2 This embodiment provides a method for preparing a UV / blue light enhanced rare earth nanocomposite material, comprising the following steps: The oleic acid-capped core-shell-shell upconversion nanoparticles prepared in Example 1 were dispersed in a hydrochloric acid solution (1 mL; 2 M) and subjected to ultrasonic treatment for 5 min to remove surface ligands. Subsequently, the product was collected by centrifugation (16,500 rpm, 20 min), washed with ethanol several times, and finally redispersed in deionized water; Pyridine-2-carboxylic acid solution (1.0 mL) was added to the ligand-free nanoparticle solution (1.0 mL, 0.1 mmol). After the mixture was sonicated for 5 hours, the obtained clear solution was centrifuged to obtain a colloidal solid, which was washed several times with ethanol and redispersed in ethanol (1.0 mL) to obtain a rare earth nanocomposite material with a pyridine-2-carboxylic acid layer on the surface.
[0051] See also Figure 4 and Figure 5 , Figure 4 This is a comparative spectrum of the luminescence intensities of the core-shell-shell rare earth nanoparticles in Example 1 of the present invention and the rare earth nanocomposite material with a pyridine-2-carboxylic acid layer in Example 2. It can be seen from the figure that the luminescence intensity of the rare earth nanocomposite material with a pyridine-2-carboxylic acid layer in Example 2 is much greater than the luminescence intensity of the core-shell-shell rare earth nanoparticles without a pyridine-2-carboxylic acid layer in Example 1.
[0052] Figure 5 The schematic diagram of energy transfer of nanomaterials with unmodified and modified pyridine-2-carboxylic acid layers shows that the pyridine-2-carboxylic acid layer forms coordination bonds with the surface rare earth ions of the rare earth nanomaterial, protecting the excitation energy and promoting energy transfer.
[0053] Example 3 This embodiment provides a method for preparing ultraviolet / blue light enhanced rare earth nanomaterials, wherein the core-shell-shell structured rare earth nanoparticles are NaYbF4:Nd@NaGdF4:Yb, Tm@NaYF4:Yb / Nd, comprising the following steps: Step A: Synthesis of NaYbF4:Nd bare core First, 0.08 mmol of Yb(CH3CO2)3·xH2O and 0.0008Nd(CH3CO2)3·xH2O aqueous solution, 10 mL of oleic acid and 10 mL of 1-octadecene liquid were added to a 50 mL three-necked flask, heated to 150 °C, and stirred for 60 min to generate a rare earth complex to obtain a precursor A solution; then, the temperature was lowered to room temperature, 6.4 mmol of sodium oleate solid powder was added to the precursor A solution, and the temperature was raised to 100 °C and stirred for 1 h under vacuum conditions; next, the mixed solution was filled with nitrogen and 3.2 mmol of NH3F solid powder was added, and the temperature was raised to 160 °C and reacted under nitrogen protection for 1.5 h; finally, the mixed solution was vacuumed for 10 min, and the temperature was raised to 320 °C for 30 min under nitrogen protection, and then cooled to room temperature, washed with anhydrous ethanol and cyclohexane, and the obtained core nanoparticles were dispersed in 4 mL cyclohexane, and the core nanoparticles NaYbF4:Nd with a diameter of 20 nm were obtained; Step B: Synthesis of NaYbF4:Nd@NaGdF4:Yb,Tm core-shell nanoparticles The molar concentration ratio is Tm 3+ :Yb 3+ :Gd 3+ =0.5:55:45, take a total of 0.4 mmol of Tm(CH3CO2)3·xH2O, Yb(CH3CO2)3·xH2O, Gd(CH3CO2)3·xH2O aqueous solution with a fixed ratio and add it to a 50 mL three-necked flask, add 5 mL of oleic acid and 5 mL of 1-octadecene liquid, heat to 150 ° C, stir for 60 min, generate rare earth complexes, and obtain precursor B solution; when the temperature drops to 80 ° C, add the core nanoparticle solution dispersed in 2 mL of cyclohexane obtained in step A to the precursor B solution, and stir for 30 min to remove cyclohexane in the system, when the temperature drops to 50 ° C, quickly add 5 mL of methanol solution containing 1 mmol NaOH and 1.36 mmol NH4F, and stir for 30 min to obtain a mixed solution; then heat the mixed solution to 100 ° C, evacuate for 5 min, and then fill with nitrogen for 1 min, and repeated three times. After removing methanol and oxygen from the reaction system, the temperature was raised to 300 °C and the reaction was carried out under the protection of nitrogen for 1.5 h. The obtained product was then cooled to room temperature and washed with anhydrous ethanol and cyclohexane to obtain NaYbF4:Nd@NaGdF4:49%Yb,1%Tm core-shell nanomaterials dispersed in 4 mL of cyclohexane with a diameter of about 30 nm. Step C: Synthesis of NaYbF4:Nd@NaGdF4:Yb, Tm@NaYF4:Yb / Nd core-shell-shell nanoparticles The molar concentration ratio is Y 3+ :Yb 3+ :Nd=90:10:1, take a total of 0.4 mmol of Y(CH3CO2)3·xH2O, Yb(CH3CO2)3·xH2O and Nd(CH3CO2)3·xH2O aqueous solutions with a fixed ratio and add them into a 50 mL three-necked flask, add 3 mL of oleic acid and 7 mL of 1-octadecene liquid, heat to 150 ℃, stir for 30-60 min to generate rare earth complexes, and obtain the shell precursor C solution. When the temperature drops to 80°C, the core-shell nanomaterial solution dispersed in 4 mL of cyclohexane obtained in step B is added to the precursor C solution, and stirred for 30 min to remove the cyclohexane in the system. When the temperature drops to 50°C, 5 mL of methanol solution containing 1 mmol NaOH and 1.36 mmol NH4F is quickly added and stirred for 30 min to obtain a mixed solution. The mixed solution is then heated to 100°C, vacuumed for 5 min, and then filled with nitrogen for 1 min, and repeated three times. After removing methanol and oxygen from the reaction system, the temperature is raised to 300°C, and the reaction is carried out under the protection of nitrogen for 1.5 h. The obtained product is then cooled to room temperature, washed with anhydrous ethanol and cyclohexane, and the obtained NaYbF4:Nd@NaGdF4:Yb, Tm@NaYF4:Yb / Nd core-shell-shell upconversion nanoparticle luminescent material is dispersed in 4 mL of cyclohexane, and the material diameter is about 40 nm.
[0054] Example 4 This embodiment provides a method for preparing a UV / blue light enhanced rare earth nanomaterial, wherein the rare earth nanoparticles with a core-shell-shell structure are NaYbF4@NaGdF4:Yb, Tm@NaYF4:Yb, and the method comprises the following steps: Step A: Synthesis of NaYbF4 bare core First, 0.8 mmol of Yb(CH3CO2)3·xH2O aqueous solution, 10 mL of oleic acid and 10 mL of 1-octadecene liquid were added to a 50 mL three-necked flask, heated to 160 °C, and stirred for 60 min to generate a rare earth complex to obtain a precursor A solution; then, the temperature was lowered to room temperature, 6.4 mmol of sodium oleate solid powder was added to the precursor A solution, and the temperature was raised to 100 °C and stirred for 1 h under vacuum conditions; next, the mixed solution was filled with nitrogen and 3.2 mmol of NH3F solid powder was added, and the temperature was raised to 150 °C and reacted under nitrogen protection for 1.0 h; finally, the mixed solution was vacuumed for 10 min, and the temperature was raised to 300 °C under nitrogen protection for 30 min, then cooled to room temperature, washed with anhydrous ethanol and cyclohexane, and the obtained core nanoparticles were dispersed in 4 mL of cyclohexane to obtain core nanoparticles NaYbF with a diameter of 20 nm. 4; Step B: Synthesis of NaYbF4@NaGdF4:Yb,Tm core-shell nanoparticles The molar concentration ratio is Tm 3+ :Yb 3+ :Gd 3+ =1:50:49, take a total of 0.4 mmol of Tm(CH3CO2)3·xH2O, Yb(CH3CO2)3·xH2O, and Gd(CH3CO2)3·xH2O aqueous solution with a fixed ratio and add it to a 50 mL three-necked flask, add 5 mL of oleic acid and 5 mL of 1-octadecene liquid, heat to 160 ° C, stir for 60 min, generate rare earth complexes, and obtain precursor B solution; when the temperature drops to 80 ° C, add the core nanoparticle solution dispersed in 2 mL of cyclohexane obtained in step A to the precursor B solution, and stir for 30 min to remove cyclohexane in the system, when the temperature drops to 50 ° C, quickly add 5 mL of methanol solution containing 1 mmol NaOH and 1.36 mmol NH4F, and stir for 30 min to obtain a mixed solution; then heat the mixed solution to 100 ° C, evacuate for 5 min, and then fill with nitrogen for 1 min, and repeated three times. After removing methanol and oxygen from the reaction system, the temperature was raised to 300 °C and the reaction was carried out under the protection of nitrogen for 1.5 h. The obtained product was then cooled to room temperature and washed with anhydrous ethanol and cyclohexane to obtain NaYbF4@NaGdF4:49%Yb,1%Tm core-shell nanomaterials dispersed in 4 mL of cyclohexane with a diameter of about 30 nm. Step C: Synthesis of NaYbF4@NaGdF4:Yb, Tm@NaYF4:Yb core-shell-shell nanoparticles The molar concentration ratio is Y 3+:Yb 3+ =85:15, take a total of 0.4 mmol of Y(CH3CO2)3·xH2O and Yb(CH3CO2)3·xH2O aqueous solution of a certain ratio and add it into a 50 mL three-necked flask, add 3 mL of oleic acid and 7 mL of 1-octadecene liquid, heat to 160 °C, stir for 30-60 min to generate a rare earth complex, and obtain the shell precursor C solution. When the temperature drops to 80°C, the core-shell nanomaterial solution dispersed in 4 mL of cyclohexane obtained in step B is added to the precursor C solution, and stirred for 30 min to remove the cyclohexane in the system. When the temperature drops to 50°C, 5 mL of methanol solution containing 1 mmol NaOH and 1.36 mmol NH4F is quickly added and stirred for 30 min to obtain a mixed solution. The mixed solution is then heated to 100°C, vacuumed for 5 min, and then filled with nitrogen for 1 min, and repeated three times. After removing methanol and oxygen from the reaction system, the temperature is raised to 300°C, and the reaction is carried out under the protection of nitrogen for 1.5 h. The obtained product is then cooled to room temperature, washed with anhydrous ethanol and cyclohexane, and the obtained NaYbF4@NaGdF4:Yb, Tm@NaYF4:Yb core-shell-shell upconversion nanoparticle luminescent material is dispersed in 4 mL of cyclohexane, and the material diameter is about 40 nm.
[0055] Example 5 In this embodiment, the application of ultraviolet / blue light enhanced rare earth nanomaterials is used for ultraviolet light induced photopolymerization reaction 3D printing technology, and the steps are as follows: (1) Synthetic liquid prepolymer Equal parts of oligocarbonate methacrylate (OCM-2) and poly(methyl methacrylate) (PMMA) were used as a photocurable composition (PCC) with 1% photoinitiator Irgacure 369. UCNPs material (rare earth nanocomposite) in ethanol was added to the photopolymerizable composition and sonicated for 10 minutes. After sonication, ethanol was evaporated by vacuum drying to obtain a liquid prepolymer. PMMA was used to increase the viscosity of the mixture and prevent nanoparticles from agglomerating. The final concentration of UCNPs was 15 mg / mL. (2) Preparation of 3D printing materials A semiconductor CW laser with a near-infrared wavelength of 980 nm was used and the laser power density was set to 15 Wcm −2. The collimated laser beam is focused by an objective lens into the PCC volume containing the embedded UCNPs. The photopolymerization reaction takes place in the local volume of the laser beam caustic, where the maximum intensity is achieved. A galvanometer scanner provides fast and precise mirror positioning for laser beam deflection in the XY plane. The displacement of the voxel along the z-coordinate is performed by a micrometer stage. After the fabrication is completed, the sample is developed in 2-propanol to remove the unpolymerized PCC material, resulting in the final 3D printed structure material. Figure 6 shown.
[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A UV / blue light enhanced rare earth nanocomposite material, characterized in that: The rare earth nanocomposite material comprises a rare earth nanomaterial and an organic coordination molecule layer arranged on the surface of the rare earth nanomaterial; the rare earth nanomaterial comprises a luminescent layer and a first energy capture layer arranged outside the luminescent layer, and an energy transfer channel is formed between the first energy capture layer and the luminescent layer; The main component of the organic coordination molecule layer is pyridine-2-carboxylic acid; The light-emitting layer contains Yb 3+ 、Tm 3+ Materials containing Yb 3+ , Gd 3+ 、Tm 3+ Materials containing Yb 3+ , Er 3+ Materials containing Gd 3+ 、Tm 3+ 、Ce 3+ At least one of the materials; The first energy capture layer contains Yb 3+ Materials containing Nd 3+ Materials containing Er 3+ Materials containing Yb 3+ With Nd 3+ at least one of the materials.
2. The ultraviolet / blue light enhanced rare earth nanocomposite material according to claim 1, characterized in that: The rare earth nanomaterial further comprises a second energy capture layer disposed inside the light-emitting layer, and an energy transfer channel is formed between the second energy capture layer and the light-emitting layer; The second energy capture layer contains Yb 3+ Materials containing Nd 3+ Materials containing Er 3+ Materials containing Yb 3+ and Nd 3+ at least one of the materials.
3. The ultraviolet / blue light enhanced rare earth nanocomposite material according to claim 2, characterized in that: The thickness of the second energy capture layer is 5-40 nm; The thickness of the light-emitting layer is 2-10 nm; The thickness of the first energy capture layer is 2-10 nm.
4. The ultraviolet / blue light enhanced rare earth nanocomposite material according to claim 2, characterized in that: The matrix materials of the second energy capture layer, the light-emitting layer and the first energy capture layer are ALnF4 or AF2, wherein A is at least one of Li, Na, K or Ca; and Ln is at least one of La, Lu, Yb, Gd or Y.
5. The ultraviolet / blue light enhanced rare earth nanocomposite material according to claim 4, characterized in that: The second energy capture layer contains Yb 3+ The molar fraction of ions is 90%~100%, or Nd 3+ The molar fraction of ions is 50%~100%, or Er 3+ The molar fraction of ions is 90%~100%; The Yb 3+ The molar fraction of ions is 30%~70%, and / or Tm 3+ The molar fraction of ions is 0.2%~1.5%, and / or Er 3+ The molar fraction of ions is 0.2%~3%, and / or Gd 3+ The molar fraction of Ce ions is 40%~60%, or 3+ The molar fraction of ions is 0.2%~5%; The first energy capture layer contains Yb 3+ The molar fraction of ions is 5%~20%, and / or Nd 3+ The molar fraction of ions is 1%~20%, or Er 3+ The molar fraction of ions is 1%~25%.
6. Use of the ultraviolet / blue light enhanced rare earth nanocomposite material as claimed in any one of claims 1 to 5 in acrylate photopolymerization.
7. The use according to claim 6, characterized in that: The rare earth nanocomposite material is used for preparing 3D printing materials.
8. The use according to claim 7, characterized in that: The preparation of the 3D printing material comprises the following steps: The rare earth nanocomposite material is mixed with a photocurable composition to form a liquid prepolymer; the prepolymer is the 3D printing material.
9. A method for preparing a UV / blue light enhanced rare earth nanocomposite material, characterized in that: The following steps are involved: S1: Preparation of rare earth nanomaterials; S2: removing the ligands on the surface of the rare earth nanomaterial to obtain a ligand-free rare earth nanomaterial, adding a pyridine-2-carboxylic acid solution to the solution of the ligand-free rare earth nanomaterial, and centrifuging to obtain a rare earth nanocomposite material.
10. The method for preparing the ultraviolet / blue light enhanced rare earth nanocomposite material according to claim 9, characterized in that: Step S1 also includes the following contents: S1.1: dissolving rare earth salt A in a solvent to obtain a precursor A; reacting the precursor A under the conditions of a sodium source and a fluorine source to obtain a second energy capture layer; S1.2: dissolving a rare earth salt B in a solvent to obtain a precursor B; mixing the second energy capture layer with the precursor B, and encapsulating the second energy capture layer in the presence of a sodium source and a fluorine source to obtain a core-shell structured nanocrystal comprising the second energy capture layer and the light-emitting layer; S1.3: Dissolve the rare earth salt C in a solvent to obtain a precursor C; mix the core-shell structured nanocrystals with the precursor C, and wrap the core-shell structured nanocrystals in the presence of a sodium source and a fluorine source to obtain a rare earth nanomaterial with a core-shell-shell structure having, from the inside to the outside, a second energy capture layer, a light-emitting layer, and a first energy capture layer.
Citation Information
Patent Citations
Near-infrared second-region luminescence enhanced rare earth nano material, preparation method and bioimaging application thereof
CN114276808A
Rare earth doped light switchable up-conversion nano-composite particle as well as preparation method and application thereof
CN116463115A